Expanding the Scope of Practice for Pharmacists in Ontario - Glen Edward Randall; Neil G. Barr; Patricia A. Wakefield; Mark G. Embrett (McMaster University Library Press, 2015)
On 15 December 2009 the Regulated Health Professions Statute Law Amendment Act, 2009 (Bill 179) received Royal Assent in Ontario. The resulting legislative amendments were intended to strengthen government oversight of the health regulatory colleges, promote interprofessional collaboration, and make better use of health professionals' existing skills and training by enhancing the scope of practice for several health professions in order to improve health system efficiency. Among the most notable scope of practice enhancements were those given to pharmacists, who would be permitted to: modify and renew existing prescriptions, prescribe a limited range of drugs independent of a physician, and administer medications such as vaccinations via injection or inhalation. The reform was driven in large part by the government's concerns related to the rising cost of health care, the public's desire for greater access to services, and demonstrated successes of similar reforms in other jurisdictions. While the Ontario reform has had some clear success, such as expanding the public's access to influenza vaccinations, to date, the evidence of achieving other goals remains weak. In particular, there is no clear evidence of improved health system efficiency and associated cost effectiveness. Moreover, it is possible that Ontario's umbrella regulatory model may be making interprofessional collaboration more, rather than less, difficult to realize. La loi de 2009 modifiant les lois en ce qui concerne les professions de santé réglementées (Loi 179) a été sanctionnée le 15 décembre 2009. Les changements législatifs résultant avaient pour but de renforcer la capacité du gouvernement de superviser les collèges des professions de santé, de promouvoir la collaboration inter-professionnelle, et de mieux utiliser les aptitudes et les formations des professionnels de santé en élargissant les domaines d'activité de plusieurs professions pour améliorer l'efficience du système. Un des èlargissements les plus notables a été celui donné aux pharmaciens et les autorisant à : modifier et renouveller des ordonnances, prescrire certains médicaments indépendamment d'un médecin, et administrer certains actes comme des vaccins par injections ou inhalations. La réforme a été guidée principalement par la volonté gouvernementale de contrôler les coûts croissants de la santé, ainsi que par le souhait d'un meilleur accès aux services dans la population, et la réussite de réformes semblables dans d'autres systèmes. Même si la réforme en Ontario a eu certains succès nets, comme d'améliorer le taux de vaccination contre la grippe, il n'existe pas vraiment de preuves que d'autres objectifs aient été atteints. En particulier, il n'existe aucune preuve claire d'amélioration de l'efficience ou de l'efficacité-coût du système de santé. En outre, il est possible que le modèle général de régulation en vigueur en Ontario rende la collaboration inter-professionnelle plus difficile au lieu de la faciliter.